Uptake and Transport of Naringenin and Its Antioxidant Effects in Human Intestinal Epithelial Caco-2 Cells - Zhang, Zhen-Dong; Tao, Qi; Qin, Zhe; Liu, Xi-Wang; Li, Shi-Hong; Bai, Li-Xia; Yang, Ya-Jun; Li, Jian-Yong (Frontiers in Nutrition, 2022)
Naringenin, a flavanone, has been reported for a wide range of pharmacological activities. However, there are few reports on the absorption, transport and antioxidant effects of naringenin. The study was to explore the uptake, transport and antioxidant effects of naringenin in vitro. Cell transmembrane resistance, lucifer yellow transmission rate, and alkaline phosphatase activity were used to evaluate the successful construction of cell model. The results showed that the absorption and transport of naringenin by Caco-2 cells were time- and concentration-dependent. Different temperatures (37 and 4°C) had a significant effect on the uptake and transport of naringenin. Verapamil, potent inhibitor of P-glycoprotein, significantly inhibit naringenin transport in Caco-2 cells. The results revealed that naringenin was a moderately absorbed biological macromolecule and can penetrate Caco-2 cells, mainly mediated by the active transport pathway involved in P-glycoprotein. At the same time, naringenin pretreatment could significantly increase the viability of H2O2-induced Caco-2 cells. Twenty four differential metabolites were identified based on cellular metabolite analysis, mainly including alanine, aspartate and glutamate metabolism, histidine metabolism, taurine and hypotaurine metabolism, pyruvate metabolism, purine metabolism, arginine biosynthesis, citrate cycle, riboflavin metabolism, and D-glutamine and D-glutamate metabolism. We concluded that the transport of naringenin by Caco-2 cells is mainly involved in active transport mediated by P-glycoprotein and naringenin may play an important role in oxidative stress-induced intestinal diseases.